Analisis Multifaktor yang Berhubungan dengan Self-Management pada Pasien Diabetic Foot Ulcer (DFU) - Nurul Maulidya; Maria Komariah; Nursiswati Nursiswati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze self-management factors in Diabetic Foot Ulcer (DFU) patients. This research uses the literature review method with keywords in EBSCO Host, Willey, Pubmed, Science Direct, and Research Gate databases. The study results obtained that the stress factor is the factor that most influences self-management in diabetic patients. Stress can be overcome by having a good level of spirituality in patients, as encouragement and motivation in carrying out good self-management. External support factors and the support of those closest to them can also motivate DFU patients to carry out self-management. Cultural and spiritual factors also influence DFU patients in carrying out and undergoing self-management in everyday life. In conclusion, stress factors, education, foot care self-care behavior, duration of DM, culture, and spirituality have a relationship to self-management of diabetic foot ulcer patients (DFU). Keywords: Diabetic Foot Ulcer, Self Management